Exercise-Induced Browning of White Adipose Tissue and Improving Skeletal Muscle Insulin Sensitivity in Obese/Non-obese Growing Mice: Do Not Neglect Exosomal miR-27a - Wang, Dongxue; Zhang, Xihuan; Li, Yibai; Jia, Lihong; Zhai, Lingling; Wei, Wei; Zhang, Li; Jiang, Hongkun; Bai, Yinglong (Frontiers in Nutrition, 2022)
Exercise is considered as a favorable measure to prevent and treat childhood obesity. However, the underlying mechanisms of exercise-induced beneficial effects and the difference between obese and non-obese individuals are largely unclear. Recently, miR-27a is recognized as a central upstream regulator of proliferator-activated receptor γ (PPAR-γ) in contributing to various physiological and pathological processes. This study aims to explore the possible cause of exercise affecting white adipose tissue (WAT) browning and reversing skeletal muscle insulin resistance in obese/non-obese immature body. For simulating the process of childhood obesity, juvenile mice were fed with basal diet or high-fat diet (HFD) and took 1h or 2h swimming exercise simultaneously for 10 weeks. Obese animal model was induced by HFD. We found that exercise hindered HFD-induced body fat development in growing mice. Exercise modified glucolipid metabolism parameters differently in obese/non-obese groups, and the changes of 2h-exercise mice were not consistent as well as 1h-exercise mice. The level of serum exosomal miR-27a in non-exercise obese group were increased obviously, which were reduced in exercise obese groups. Results from bioinformatics analysis and dual-luciferase reporter assay showed that miR-27a targeted PPAR-γ. Exercise stimulated WAT browning, however, the response of obese WAT lagged behind normal WAT. 2h-exercise activated IRS-1/Akt/GLUT-4 signaling pathway in skeletal muscle of HFD fed mice. In summary, our findings confirmed that exercise-induced beneficial effects are associated with exercise duration, and the response of obese and non-obese body is different. Exosomal miR-27a might be a crucial node for the process of exercise-induced browning of WAT and improving skeletal muscle insulin sensitivity.